PENERAPAN SISTEM KOMPUTERISASI HAJI TERPADU (SISKOHAT) TERHADAP PENINGKATAN LAYANAN HAJI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SUMBAWA - Suzami, Ardi; Hudaya, Chairul; Rodianto (Jurnal TAMBORA, 2021)
This study aims to determine the effect of the implementation of the Integrated Hajj Computerized System (SISKOHAT) on the improvement of Hajj services at the Ministry of Religion Office of Sumbawa Regency. This research is quantitative descriptive. The type of data used, namely primary data, was obtained from the results of distributing questionnaires to prospective pilgrims, the general public, and SISKOHAT officers/managers in Sumbawa Regency. The sample in this study were 101 respondents who were prospective pilgrims, 113 respondents who were the general public, and 11 respondents who were SISKOHAT officers/managers. The data analysis method used is simple linear regression analysis which includes data quality test, classical assumption test, and coefficient of determination test. The results showed that the application of SISKOHAT had a positive and significant effect on Hajj services. In addition, the implementation of SISKOHAT has an effect of 82.1% on increasing hajj services for prospective pilgrims, 57.3% for the general public, and 52.6% for SISKOHAT officers/managers. The remaining 17.9% for prospective pilgrims, 42.7% for the general public, and 47.4% for SISKOHAT officers/managers are influenced by other variables not discussed in this study.